Cryo-ET suggests tubulin chaperones form a subset of microtubule lumenal particles with a role in maintaining neuronal microtubules - Saikat Chakraborty; Antonio Martinez-Sanchez; Florian Beck; Mauricio Toro-Nahuelpan; In-Young Hwang; Kyung-Min Noh; Wolfgang Baumeister; Julia Mahamid (Proceedings of the National Academy of Sciences, 2025)
The functional architecture of the long-lived neuronal microtubule (MT) cytoskeleton is maintained by various MT-associated proteins (MAPs), most of which are known to bind to the MT outer surface. However, electron microscopy (EM) has long ago revealed the presence of particles inside the lumens of neuronal MTs, of yet unknown identity and function. Here, we use cryogenic electron tomography (cryo-ET) to analyze the three-dimensional (3D) organization and structures of MT lumenal particles in primary hippocampal neurons, human induced pluripotent stem cell–derived neurons, and pluripotent and differentiated P19 cells. We obtain in situ density maps of several lumenal particles from the respective cells and detect common structural features underscoring their potential overarching functions. Mass spectrometry-based proteomics combined with structural modeling suggest that a subset of lumenal particles could be tubulin-binding cofactors (TBCs) bound to tubulin monomers. A different subset of smaller particles, which remains unidentified, exhibits densities that bridge across the MT protofilaments. We show that increased lumenal particle concentration within MTs is concomitant with neuronal differentiation and correlates with higher MT curvatures. Enrichment of lumenal particles around MT lattice defects and at freshly polymerized MT open-ends suggests a MT protective role. Together with the identified structural resemblance of a subset of particles to TBCs, these results hint at a role in local tubulin proteostasis for the maintenance of long-lived neuronal MTs.